Clinical Burden and Unmet Need in Recurrent Pericarditis: A Systematic Literature Review. Issue 2 (March 2022) - Klein, Allan; Cremer, Paul; Kontzias, Apostolos; Furqan, Muhammad; Forsythe, Anna; Crotty, Christopher; Lim-Watson, Michelle; Magestro, Matthew
Abstract : Inflammation of the pericardium (pericarditis) is characterized by excruciating chest pain. This systematic literature review summarizes clinical, humanistic, and economic burdens in acute, especially recurrent, pericarditis, with a secondary aim of understanding United States treatment patterns and outcomes. Short-term clinical burden is well characterized, but long-term data are limited. Some studies report healthcare resource utilization and economic impact; none measure health-related quality-of-life. Pericarditis is associated with infrequent but potentially life-threatening complications, including cardiac tamponade (weighted average: 12.7% across 10 studies), constrictive pericarditis (1.84%; 9 studies), and pericardial effusion (54.7%; 16 studies). There are no approved pericarditis treatments; treatment guidelines, when available, are inconsistent on treatment course or duration. Most recommend first-line use of conventional treatments, for example, nonsteroidal antiinflammatory drugs with or without colchicine; however, 15–30% of patients experience recurrence. Second-line therapy may involve conventional therapies plus long-term utilization of corticosteroids, despite safety issues and the difficulty of tapering or discontinuation. Other exploratory therapies (eg, azathioprine, immunoglobulin, methotrexate, anakinra) present steroid-sparing options, but none are supported by robust clinical evidence, and some present tolerability challenges that may impact adherence. Pericardiectomy is occasionally pursued in treatment-refractory patients, although data are limited. This lack of an evidence-based treatment pathway for patients with recurrent disease is reflected in readmission rates, for example, 12.2% at 30 days in 1 US study. Patients with continued recurrence and inadequate treatment response need approved, safe, accessible treatments to resolve pericarditis symptoms and reduce recurrence risk without excessive treatment burden. Abstract : Supplemental Digital Content is available in the text.